Immune status of dairy calves in the Northern Plains of Costa Rica. Year I. - Sánchez-Salas, Jeffry; Elizondo-Salazar, Jorge Alberto; Arroyo-Quesada, Geovanny (Agronomía Mesoamericana, 2012)
The objective of this study was to characterize the immune status of dairy calves in the Northern Plains of Costa Rica. For the purpose of this study, failure of passive immunity was considered when TSP concentration was less than 5.5 g/dl. TSP concentration ranged from 2.8 to 11.0, with an overall mean of 6.2 g/dl. Of all the animals evaluated, 31.8% had failure of passive transfer. When considering sex of the calves, 31.4% of females and 25.3% of males failed to obtain adequate levels of immunity and concentration of TSP showed significant differences (6.2 vs. 5.9 g/dl, respectively). Calves born to Holstein x Jersey crosses had significant higher TSP concentrations than calves born to Holstein dams. When considering calving of the d